E-MARKETPLACE UMKM MENGHADAPI REVOLUSI INDUSTRI 4.0 DALAM PERSPEKTIF ISLAM - Husnurrosyidah, Husnurrosyidah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
This study aims to determine the condition of the development of virtual use in the marketing of MSME products in the era of the industrial revolution 4.0 in Kudus, the extent of the realization of e-marketplaces in MSMEs, inhibiting and supporting factors of MSMEs in implementing e-marketplaces in Kudus, and the application of sharia values in practice the use of e-marketplaces by SMEs in Kudus. This research is a field research with a qualitative approach. Data sources used are primary and secondary data. The informants of this research are the officials of the Ministry of Industry and Trade, and the Manpower Office and Small and Medium Enterprises as well as SMEs and consumers. Data collection techniques use interviews and documentation. The results of the study show: 1) In the era of digitization, the Kudus District Trade Office created a platform; 2) The inhibiting factors for the implementation of E-Marketplace in Kudus are (a) Media limitations for online; (b) Limited Manpower; (c) Limitations of Internet Connection; (d) Duration of Delivery; (e) Limited human resources owned by MSME in Kudus to enter the digital market; (f) Lack of Coordination among Departments in Kudus Regency; (g) Competitive Atmosphere of Competitors. Factors supporting the implementation of e-marketplaces at MSMEs in Kudus are (a) the uniqueness of Kudus MSME products; (b) Ease of Technology in Kudus; (c) Government support for MSMEs facing the era of digitalization; 3) SMEs in Kudus have applied the principles of Islamic entrepreneurs, namely the principle of monotheism, justice, the existence of maslahah activities and the principle of taawun.